Jual Beli Online dalam Prespektif Alquran - Galib, Mukhtar; -, Maulana; Abubakar, Achmad; Irham, Muhammad (Indonesian Journal of Islamic Economics and Business, 2024)
Abstract The purpose of this research is to gain a comprehensive understanding of online buying and selling practices from the perspective of the Quran. This study involves the analysis of principles outlined in the Quran that can be applied to online commerce in the present-day context. The research findings demonstrate that online transactions, when examined through the lens of the Quran, should adhere to principles of justice, honesty, transparency, avoidance of usury, consumer protection, and contract fulfillment. While the Quran does not explicitly address online buying and selling, the principles contained within it can be effectively applied to ensure that these transactions align with Islamic values. The research underscores the significance of consulting qualified experts in interpretation (tafsir) and Islamic jurisprudence (fiqh) to attain a deeper understanding of these principles within the specific context of online commerce. By adhering to the Quranic principles, individuals engaging in online buying and selling can foster an environment of fairness, integrity, and ethical conduct. This research serves as a valuable guide for Muslims seeking to navigate the realm of online commerce in a manner that upholds the teachings and values of Islam. It highlights the importance of incorporating the Quranic principles into contemporary business practices and emphasizes the need for continuous consultation with experts to ensure a comprehensive understanding of these principles in the context of online buying and selling. Keywords: Online transactions, Quranic perspective, Principles, Islamic values